Integrated of Aerodinamics Tip and Hub of Wind Turbine on Composite Materials - Akhmad Riszal; Agus Sugir; Martinus; Ahmad Yonanda (Journal of Applied Science, Engineering and Technology, 2025)
Global energy consumption is increasing, this is because human needs are dependent on electricity. However, many power plants still depend on fossil fuels, so the impact on the environment is getting bigger as energy consumption increases. It is necessary to develop renewable energy sources, to reduce the use of fossil fuels. One of them is using renewable energy from wind sources. The purpose of this research is to conduct simulations to analyze the aerodynamics and pressure distribution in the tip and hub areas of a wind turbine using QBlade, then conduct experiments in making composite specimens that will later be applied to wind turbines according to the design. This research shows that the highest pressure occurs at the tip and hub of the blade, so it is necessary to improve strong and lightweight materials by using bamboo fiber composites.